Taxpayer Compliance Factors: Tax Awareness, Will, Socialization and Sanctions - Rahayu, Yayuk Ngesti (Archives of Business Research, 2022)
This study goals to study the dominant factors influencing taxpayer compliance from internal factors, namely the awareness and willingness of taxpayers; external factors, particularly from the socialization of taxation and tax sanctions. The survey was once conducted on taxpayers who follow for land certificates at the State Land Agency of Malang City, East Java, Indonesia. Analysis tool the usage of WarpPLS version 7.0 to test Outer model: convergent validity, composite reliability; Inner mannequin through figuring out R-Square and Q2. The consequences show that the Fit and Quality Indices Model of taxpayer compliance which is built based on awareness, willingness, tax socialization and tax sanctions is good. Willingness to pay taxes and tax sanctions play a role in influencing taxpayer compliance, whilst taxpayer recognition and tax socialization do not have an effect on taxpayer compliance.